2014
DOI: 10.1073/pnas.1417347111
|View full text |Cite
|
Sign up to set email alerts
|

Timing the impact of literacy on visual processing

Abstract: Learning to read requires the acquisition of an efficient visual procedure for quickly recognizing fine print. Thus, reading practice could induce a perceptual learning effect in early vision. Using functional magnetic resonance imaging (fMRI) in literate and illiterate adults, we previously demonstrated an impact of reading acquisition on both high-and low-level occipitotemporal visual areas, but could not resolve the time course of these effects. To clarify whether literacy affects early vs. late stages of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 72 publications
6
89
2
2
Order By: Relevance
“…Comparison of literate and illiterate adults has established that learning to recognize letter strings produced a modest but significant competition with face and checkerboard stimuli at the canonical site of the VWFA, resulting in shrinking of face-selective responses to within 10 mm of the VWFA and a shift to right-hemisphere FFA ( [20], see also [34,35] for a similar observation reported in the comparison of the responses of dyslexic and normal readers at 9 years of age). In a follow-up study with the same adult subjects, the posterior arcuate fasciculuswhich connects the VWFA to posterior superior temporal and inferior parietal regions involved in phonological representations (among others) -was found to be reinforced by the acquisition of literacy [36].…”
Section: Box 2 Deep Learning Network and Symbol Form Areasmentioning
confidence: 65%
“…Comparison of literate and illiterate adults has established that learning to recognize letter strings produced a modest but significant competition with face and checkerboard stimuli at the canonical site of the VWFA, resulting in shrinking of face-selective responses to within 10 mm of the VWFA and a shift to right-hemisphere FFA ( [20], see also [34,35] for a similar observation reported in the comparison of the responses of dyslexic and normal readers at 9 years of age). In a follow-up study with the same adult subjects, the posterior arcuate fasciculuswhich connects the VWFA to posterior superior temporal and inferior parietal regions involved in phonological representations (among others) -was found to be reinforced by the acquisition of literacy [36].…”
Section: Box 2 Deep Learning Network and Symbol Form Areasmentioning
confidence: 65%
“…Proverbio et al (2013) found that left fusiform activations to words were about one centimeter more anterior in musicians than in controls, without assessing the significance of this difference and using the spatially imprecise method of event-related potentials. Another example of interaction between categories of visual objects in defining the layout of cortical specialization was reported by Dehaene et al (2010), who showed that literacy was correlated with a shrinking of face-selective areas contiguous to the VWFA, and an increase in face-induced activation in the right FFA (see also Plaut and Behrmann, 2011;Pegado et al, 2014). Srihasam et al (2014) showed that when monkeys learned a second symbol set, activations induced by a first-learned set moved away slightly, again suggestive of competition between categories for cortical space.…”
Section: Impact Of Musical Expertise On the Processing Of Wordsmentioning
confidence: 91%
“…knife, hair-dryer) presented in a normal orientation. The faces, tools, and houses images used here were used in previous studies in order to map category selectivity in the occipitotemporal cortex (Gaillard et al, 2006;Thirion et al, 2007;Dehaene et al, 2010;Pegado et al, 2014;Pinel et al, 2015). Music notation corresponded to one bar of classical piano music (G and F clefs), containing no alphabetic symbol.…”
Section: Stimulimentioning
confidence: 99%
“…For example, the face-response displacement effect: as literacy increases, face-induced functional magnetic resonance imaging (fMRI) responses in the left fusiform face area (FFA) become slightly smaller but increase substantially in the classical right FFA [26]. This effect was replicated in an fMRI study on children [27] and ERP studies on children and adults [28,29]. Moreover, there were some overlaps of neural selectivity between faces and words in early perceptual processing [30].…”
Section: Introductionmentioning
confidence: 94%